Transcatheter non-acute retrieval of the tine-based leadless ventricular pacemaker - Funasako, Moritoshi; Hála, Pavel; Janotka, Marek; Šorf, Jan; Machová, Lucie; Petrů, Jan; Chovanec, Milan; Škoda, Jan; Šedivá, Lucie; Šimon, Jaroslav; Dujka, Libor; Reddy, Vivek Y; et al. (Europace, 2024)
AIMS: We report our single-centre experience of mid-term to long-term retrieval and reimplantation of a tine-based leadless pacemaker [Micra transcatheter pacing system (TPS)]. The TPS is a clinically effective alternative to transvenous single-chamber ventricular pacemakers. Whereas it is currently recommended to abandon the TPS at the end of device life, catheter-based retrieval may be favourable in specific scenarios. METHODS AND RESULTS: We report on nine consecutive patients with the implanted TPS who subsequently underwent transcatheter retrieval attempts. The retrieval system consists of the original TPS delivery catheter and an off-the-shelf single-loop 7 mm snare. The procedure was guided by fluoroscopy and intracardiac echocardiography. After an implantation duration of 3.1 ± 2.8 years (range 0.4-9.0), the overall retrieval success rate was 88.9% (8 of 9 patients). The mean procedure time was 89 ± 16 min, and the fluoroscopy time was 18.0 ± 6.6 min. No procedure-related adverse device events occurred. In the one unsuccessful retrieval, intracardiac echocardiography revealed that the TPS was partially embedded in the ventricular tissue surrounding the leadless pacemaker body in the right ventricle. After retrieval, three patients were reimplanted with a new TPS device. All implantations were successful without complications. CONCLUSION: A series of transvenous late retrievals of implanted TPS devices demonstrated safety and feasibility, followed by elective replacement with a new leadless pacing device or conventional transvenous pacing system. This provides a viable end-of-life management alternative to simple abandonment of this leadless pacemaker.
Keywords: Device Removal; Cardiac Catheters; kardiostimulace umělá; časové faktory; senioři; Aged; Male; lidé; Treatment Outcome; lidé středního věku; Humans; Leadless cardiac pacemaker; Cardiac Pacing, Artificial; intervenční radiografie; Middle Aged; Leadless pacemaker retrieval; Echocardiography; odstranění implantátu; srdeční katetrizace; senioři nad 80 let; Micra transcatheter pacing system; Aged, 80 and over; Time Factors; srdeční katétry; mužské pohlaví; výsledek terapie; Cardiac Catheterization; Equipment Design; design vybavení; echokardiografie; Pacemaker, Artificial; ženské pohlaví; kardiostimulátor; Female; Leadless pacemaker reimplantation; Radiography, Interventional